Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti dengan Metode Problem Based Learning pada Materi Perempuan dan Laki-Laki Diciptakan Sebagai Citra Allah Fase C Kelas V SD Negeri 5 Batas Nangka - Bernadeta Tesa (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education and Character Education subjects through the Problem Based Learning (PBL) method for fifth-grade students at SDN 5 Batas Nangka during the 2024/2025 academic year. This research is a Classroom Action Research (CAR) conducted in two cycles, with one meeting in each cycle. Each cycle consists of several stages: planning, action implementation, observation, and reflection. The first and second cycles cover the topics of "Men and Women Created in the Image of God," focusing on their different duties and roles, and the material "Concept of Men and Women Created in the Image of God" based on Genesis 1:26-27. The subjects of this study are seven fifth-grade Catholic religious education students at SDN 5 Batas Nangka. Data collection techniques used were observation and tests. The results indicate that the implementation of the PBL method significantly improved learning outcomes from the first to the second cycle. In the first cycle, the affective aspect of students showed 57.14% in the capable category and 42.86% in the adequate category, increasing to 100% in the capable category in the second cycle. In the cognitive aspect, students scored 28.57% in the proficient category, 28.57% in the capable category, and 42.86% in the adequate category, which increased to 42.86% in the proficient category and 57.14% in the capable category in the second cycle. For the psychomotor aspect, students showed 71.43% in the capable category and 28.57% in the adequate category, which increased to 42.86% in the proficient category and 57.14% in the capable category in the second cycle. The conclusion of this study is that the implementation of the PBL method can enhance the learning outcomes of Catholic Religious Education and Character Education for fifth-grade students at SDN 5 Batas Nangka.